Research on satisfaction of Vietnamese university lecturers - Trung, Ngo Sy; Binh, Tran Van; Tuyet, Kinh Thi; Thuan, Nguyen Thi Thai; Hao, Nguyen Thi; Vi, Thai Thi Tuong; Suong, Pham Thi Nguyet; Duyen, Ngo Thi; Thao, Nguyen Thi Huong; Tung, Phuong Huu (Edelweiss Applied Science and Technology, 2024)
For universities, lecturers are the human resources who directly carry out the training task to create human resource training products for society; lecturers play an important role in determining the strategic development of the school. Universities that motivate lecturers to work will create satisfaction for lecturers, promote creativity to contribute to the school. This study addresses the job satisfaction of lecturers, including public universities and non-public universities to identify and compare the differences in job satisfaction of lecturers at universities in Vietnam. The author uses quantitative methods through a survey of 800 lecturers from 10 universities in Vietnam to collect data for the study. The research results show that salary, work itself, development opportunities, recognition, relationships at work, working environment and conditions have an impact on the job satisfaction of lecturers. However, the level of impact of each factor on the satisfaction of lecturers at public universities is different from that of lecturers at non-public universities; showing a clear difference in job satisfaction of lecturers at two types of universities in Vietnam. With the results of this research, the author finds that salary, work itself, development opportunities, recognition, relationships at work, working environment and conditions have an impact on the job satisfaction of lecturers at non-public universities; lecturer satisfaction also contributes significantly to the success of universities, it determines the quality of higher education, promotes innovation in universities.